Glosa do postanowienia SN z dnia 22 września 2023 r., I CSK 3637/22.Udzielanie przez sąd pouczeń w trybie art. 5 KPC - Rzewuski, Maciej (PRAWO i WIĘŹ, 2026)
The subject of the study is the validity of providing procedural instructions by a civil court. This matter is neither simple nor devoid of practical doubts. In the context of civil cases being heard, concerns often arise regarding the correct application of the provisions of Art. 5 of the Code of Civil Procedure. These doubts usually focus on the answer to the question whether providing procedural instructions is still a right or perhaps an obligation of the civil court. The Supreme Court attempted to answer this question in the context of the voted decision. The aim of the work will be to approve the position expressed therein.